Unidades fraseológicas - ¿qué si no? Phraseologische Sprachbewusstheit entwickeln, in: Der Fremdsprachliche Unterricht Spanisch - Bürgel, Christoph

Förderung der mündlichen Sprachproduktion im Fremdsprachenunterricht. Perspektiven aus Wissenschaft und Praxis, in: bzf 69, 85-88. - Bürgel, Christoph; Schlaak, Claudia; Willems, Aline

- Digitalisierung als Wunderwaffe - Bürgel, Christoph; Siepmann, Dirk (FAZ)

 Zeitschrift für Romanische Sprachen und ihre Didaktik, ( Zeitschrift für Romanische Sprachen und ihre Didaktik)

AuroraFlow, an Easy-to-Use, Low-Latency FPGA Communication Solution Demonstrated on Multi-FPGA Neural Network Inference - Pape, Gerrit; Wintermann, Bjarne; Jungemann, Linus; Lass, Michael; Meyer, Marius; Riebler, Heinrich; Plessl, Christian (Proceedings of the 15th International Symposium on Highly Efficient Accelerators and Reconfigurable Technologies)

Evaluating the Strong Scaling Potential of AI Engines for Molecular Dynamics Simulations - Bröker, Mika; Menzel, Johannes; Plessl, Christian (Proceedings of the 15th International Symposium on Highly Efficient Accelerators and Reconfigurable Technologies)

Experimental and numerical investigation of the influence of rolling-induced sheet metal deformation on SPR joints - Schlichter, Malte Christian; Harabati, Özcan; Ludwig, Jean-Patrick; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Materials Research Proceedings)
Abstract. In the development of advanced lightweight automotive solutions, self-piercing riveting (SPR) offers the possibility of joining multi-material structures to fulfil a wide variety of requirements. With regard to the entire process chain, production-related pre-deformations of the parts to be joined can influence the geometric shape and load capacity of SPR joints. Various studies have investigated the influence of pre-stretched sheet materials, in the sense of pre-drawing processes, on the formation of SPR joints. The impact of pre-stretching sheet metals on the formation of their geometrical characteristics and the shear-tensile strength of SPR processes was observed [1]. Pre-rolled semi-finished products are also joined together in mixed material automotive structures, e.g. tailor rolled blanks. This work aims to investigate the influence of pre-rolled joining parts on the geometric formation and load-carrying capacity of SPR joints. For this purpose, sheets of metal are cold-formed using a rolling process to induce a defined strain-hardening state in the material and then joined in various combinations. As the degree of deformation increases, the rolling of samples can lead to minimal accumulation of damage in the sheet materials, which can influence the joint behaviour. The rolling process, as well as the subsequent joining process, are also investigated by FEM. The influence of pre-rolled semi-finished products on the strength of the SPR joints is investigated.

Resonant and antiresonant exciton-phonon coupling in quantum dot molecules - Lienhart, Michelle; Gawarecki, Krzysztof; Stöcker, Markus; Bopp, Frederik; Cullip, Charlotte; Akhlaq, Nadeem; Thalacker, Christopher; Schall, Johannes; Rodt, Sven; Ludwig, Arne; Reuter, Dirk; Reitzenstein, Stephan; et al. (Physical Review B)
Spins confined in optically active quantum dot molecules (QDMs) can be used for the deterministic generation of photonic graph states with tailored entanglement structures. Their usefulness for the generation of such nonclassical states of light is determined by orbital and spin decoherence mechanisms, particularly phonon-mediated processes dominant at energy scales up to a few millielectronvolts. Here, we directly measure the spectral function of orbital phonon relaxation between the energy states of the neutral exciton in a QDM and benchmark our findings against microscopic <a:math xmlns:a="http://www.w3.org/1998/Math/MathML"> <a:mrow> <a:mi mathvariant="bold-italic">k</a:mi> <a:mo>·</a:mo> <a:mi mathvariant="bold-italic">p</a:mi> <a:mspace width="4pt"/> </a:mrow> </a:math> theory. Our results reveal pronounced resonances and antiresonances in the phonon-relaxation rates, ranging from tens of <e:math xmlns:e="http://www.w3.org/1998/Math/MathML"> <e:mrow> <e:mi>µ</e:mi> <e:msup> <e:mrow> <e:mi mathvariant="normal">s</e:mi> </e:mrow> <e:mrow> <e:mo>−</e:mo> <e:mn>1</e:mn> </e:mrow> </e:msup> </e:mrow> </e:math> up to tens of <g:math xmlns:g="http://www.w3.org/1998/Math/MathML"> <g:msup> <g:mrow> <g:mi>ns</g:mi> </g:mrow> <g:mrow> <g:mo>−</g:mo> <g:mn>1</g:mn> </g:mrow> </g:msup> </g:math> . Comparison with a kinetic model reveals the voltage (energy) dependent phonon coupling strength and fully explains the interplay between phonon-assisted relaxation and radiative recombination. The resonances and antiresonances enable further tunability of the exciton lifetime which can be leveraged to increase the lifetime of energetically unfavorable charge configurations needed for realizing efficient spin-photon interfaces and multidimensional cluster states.

Quantum 2-SAT on low dimensional systems is $\mathsf{QMA}_1$-complete: Direct embeddings and black-box simulation - Rudolph, Dorian; Gharibian, Sevag; Nagaj, Daniel (16th Innovations in Theoretical Computer Science (ITCS))
Despite the fundamental role the Quantum Satisfiability (QSAT) problem has played in quantum complexity theory, a central question remains open: At which local dimension does the complexity of QSAT transition from "easy" to "hard"? Here, we study QSAT with each constraint acting on a $k$-dimensional and $l$-dimensional qudit pair, denoted $(k,l)$-QSAT. Our first main result shows that, surprisingly, QSAT on qubits can remain $\mathsf{QMA}_1$-hard, in that $(2,5)$-QSAT is $\mathsf{QMA}_1$-complete. In contrast, $2$-SAT on qubits is well-known to be poly-time solvable [Bravyi, 2006]. Our second main result proves that $(3,d)$-QSAT on the 1D line with $d\in O(1)$ is also $\mathsf{QMA}_1$-hard. Finally, we initiate the study of 1D $(2,d)$-QSAT by giving a frustration-free 1D Hamiltonian with a unique, entangled ground state. Our first result uses a direct embedding, combining a novel clock construction with the 2D circuit-to-Hamiltonian construction of [Gosset, Nagaj, 2013]. Of note is a new simplified and analytic proof for the latter (as opposed to a partially numeric proof in [GN13]). This exploits Unitary Labelled Graphs [Bausch, Cubitt, Ozols, 2017] together with a new "Nullspace Connection Lemma", allowing us to break low energy analyses into small patches of projectors, and to improve the soundness analysis of [GN13] from $Ω(1/T^6)$ to $Ω(1/T^2)$, for $T$ the number of gates. Our second result goes via black-box reduction: Given an arbitrary 1D Hamiltonian $H$ on $d'$-dimensional qudits, we show how to embed it into an effective null-space of a 1D $(3,d)$-QSAT instance, for $d\in O(1)$. Our approach may be viewed as a weaker notion of "simulation" (à la [Bravyi, Hastings 2017], [Cubitt, Montanaro, Piddock 2018]). As far as we are aware, this gives the first "black-box simulation"-based $\mathsf{QMA}_1$-hardness result, i.e. for frustration-free Hamiltonians.

Sprachbezogene Kompetenzerwartungen im Sportunterricht – Eine systematische Lehrplananalyse - Grimminger-Seidensticker, Elke; Treder, Alexandra; Niederhaus, Constanze (Zeitschrift für Sportpädagogische Forschung)

Beating Grover search for low-energy estimation and state preparation - Buhrman, Harry; Gharibian, Sevag; Landau, Zeph; Gall, François Le; Schuch, Norbert; Tamaki, Suguru (Physical Review Letters)
Estimating ground state energies of many-body Hamiltonians is a central task in many areas of quantum physics. In this work, we give quantum algorithms which, given any $k$-body Hamiltonian $H$, compute an estimate for the ground state energy and prepare a quantum state achieving said energy, respectively. Specifically, for any $ε>0$, our algorithms return, with high probability, an estimate of the ground state energy of $H$ within additive error $ε M$, or a quantum state with the corresponding energy. Here, $M$ is the total strength of all interaction terms, which in general is extensive in the system size. Our approach makes no assumptions about the geometry or spatial locality of interaction terms of the input Hamiltonian and thus handles even long-range or all-to-all interactions, such as in quantum chemistry, where lattice-based techniques break down. In this fully general setting, the runtime of our algorithms scales as $2^{cn/2}$ for $c<1$, yielding the first quantum algorithms for low-energy estimation breaking the natural bound based on Grover search. The core of our approach is remarkably simple, and relies on showing that any $k$-body Hamiltonian has a low-energy subspace of exponential dimension.

Energy, Bosons and Computational Complexity - Chabaud, Ulysse; Gharibian, Sevag; Mehraban, Saeed; Motamedi, Arsalan; Naeij, Hamid Reza; Rudolph, Dorian; Sambrani, Dhruva (arXiv:2510.08545)
We investigate the role of energy, i.e. average photon number, as a resource in the computational complexity of bosonic systems. We show three sets of results: (1. Energy growth rates) There exist bosonic gate sets which increase energy incredibly rapidly, obtaining e.g. infinite energy in finite/constant time. We prove these high energies can make computing properties of bosonic computations, such as deciding whether a given computation will attain infinite energy, extremely difficult, formally undecidable. (2. Lower bounds on computational power) More energy ``='' more computational power. For example, certain gate sets allow poly-time bosonic computations to simulate PTOWER, the set of deterministic computations whose runtime scales as a tower of exponentials with polynomial height. Even just exponential energy and $O(1)$ modes suffice to simulate NP, which, importantly, is a setup similar to that of the recent bosonic factoring algorithm of [Brenner, Caha, Coiteux-Roy and Koenig (2024)]. For simpler gate sets, we show an energy hierarchy theorem. (3. Upper bounds on computational power) Bosonic computations with polynomial energy can be simulated in BQP, ``physical'' bosonic computations with arbitrary finite energy are decidable, and the gate set consisting of Gaussian gates and the cubic phase gate can be simulated in PP, with exponential bound on energy, improving upon the previous PSPACE upper bound. Finally, combining upper and lower bounds yields no-go theorems for a continuous-variable Solovay--Kitaev theorem for gate sets such as the Gaussian and cubic phase gates.

Quantum k-SAT Related Hypergraph Problems - Kremer, Simon-Luca; Rudolph, Dorian; Gharibian, Sevag (arXiv:2506.17066)
The Quantum k-SAT problem is the quantum generalization of the k-SAT problem. It is the problem whether a given local Hamiltonian is frustration-free. Frustration-free means that the ground state of the k-local Hamiltonian minimizes the energy of every local interaction term simultaneously. This is a central question in quantum physics and a canonical QMA_1-complete problem. The Quantum k-SAT problem is not as well studied as the classical k-SAT problem in terms of special tractable cases, approximation algorithms and parameterized complexity. In this paper, we will give a graph-theoretic study of the Quantum k-SAT problem with the structures core and radius. These hypergraph structures are important to solve the Quantum k-SAT problem. We can solve a Quantum k-SAT instance in polynomial time if the derived hypergraph has a core of size n-m+a, where a is a constant, and the radius is at most logarithmic. If it exists, we can find a core of size n-m+a with the best possible radius in polynomial time, whereas finding a general minimum core with minimal radius is NP-hard.

Ultrasound based measurement of mechanical properties of continuous fiber reinforced thermoplastic laminates – A non-destructive method to identify changes in fiber matrix adhesion - Moritzer, Elmar; Brandes, Philipp; Claes, Leander; Henning, Bernd (PIAE EUROPE 2025)

Zerstörungsfreie Ultraschall-Prüfung von Organoblechen - Moritzer, Elmar; Brandes, Philipp; Westphal, Max Siegfried; Claes, Leander; Wippermann, Mareen; Düchting, Julia; Henning, Bernd (WAK Jahresmagazin)
Keywords: Faser-Kunststoff-Verbunde (FKV); Faserverstärkte Kunststoffe (FVK); Organobleche; Ultraschall

Professionalisierung (angehender) Lehrkräfte für sprachbildenden Fachunterricht im Berufsfeld Ernährung und Hauswirtschaft mittels OER-Lektionen. - Meyer, Anja; Dehn, Freya; Gövert, Andre; Schlegel-Matthies, Kirsten; Niederhaus, Constanze (Sprache(n) im Beruf: Gestaltung und Förderung beruflicher Sprachbildung an den verschiedenen Lernorten.)

Band Switching for Mobile Energy Optimization in 5G Networks and Beyond - Illian, Marvin; Luchterhandt, Björn; Wang, Lin (Proceedings of the 20th Workshop on Mobility in the Evolving Internet Architecture (MobiArch))

DFG fördert Forschungsprojekt - klare Wissensstrukturen in der Wirtschaftsinformatik - Kundisch, Dennis

Improvement of Wind Power Utilization Through Flexible Operation of Data Center in Wind Parks - Ahmadi, Mehdi; Knorr, Lukas; Meschede, Henning (Renewable Energy)

Graph Neural Network Surrogates for Uncertainty Quantification in Multi-Node Energy System modeling - Prina, Matteo Giacomo; Knorr, Lukas; Schlosser, Florian; Meschede, Henning; Misconel Schreiber, Steffi; Manepace, Andrea; Sparber, Wolfram